THE DEATH PENALTY FORMULATION POLICY ON THE NARCOTICS CRIME ACT IN INDONESIA - I Wayan Wardana (Jurnal IUS Kajian Hukum dan Keadilan, 2014)
The International narcotic criminal acts are at a dangerous level of society,  state and nation even world peace. In efforts to overcome the narcotic criminal act through criminal law instrument,  the Indonesian government has adopted a policy by issuing the Acts Number 35 Year 2009 on Narcotics that in the criminal provisions include a death penalty. The issues raised in this research is,  how the legal basis of the death penalty guidelines in the Acts Number 35 Year 2009 on Narcotics?,  and whether the death penalty still need be formulated in the narcotic criminal act of Indonesia in the future?. The method used is the normative legal research with the legislation approach (statutory approach),  conceptual approaches,  and the comparative approach. The legal basis of the death penalty guidelines in Acts Number 35 Year 2009 on Narcotics is not yet regulated limitedly and still based on Article 11 of the Criminal Code as amended in the Acts Number 2/Pnps/1964,  namely Presidential Decree Number 2 Year 1964 that determined base on the Acts Number 5 Year 1969 on the Implementation Procedure of the Death Penalty that imposed by the Court in the in the General Court and the Military area,  and the Police Regulation Number 12 Year 2010 on the Implementation Procedure of the Death Penalty. The Death penalty still need to be formulated in the narcotic criminal act of Indonesia in the future with the reason that : the application of the death punishment is not contrary to religion,  Pancasila,  and human rights. Therefore death penalty sanctions are still preserved in the bill of Criminal Code Year 2012,  and narcotics criminal act offenses views of its extraordinary impact is very complex.Keywords : Formulation Policy of Dead Penalty,  Narcotics Crime.